Horror cinema and sadistic spectacle: A further defense of gorefests - Marius A. Pascale (Cogent Arts & Humanities, 2023)
AbstractDismemberment via chainsaw, consuming organs from a living person, turning a body inside out via spectral hooks. Horror cinema is no stranger to intense, often controversial imagery. Significant concerns arise over “gorefests,” a horror subgenre rife with graphic violence, taboo subjects, and extreme terror. Modern gorefest opponents appeal to the Argument from Reactive Attitudes, a model that recriminates the subgenre and its viewers due to the presumption that engaging will negatively influence moral attitudes. Ian Stoner rejects the ARA’s reasoning for why gorefests meet necessary criteria for moral concern. While Stoner’s defense is an instrumental contribution to horror ethics discourse, his argument contains flaws. I present four objections focused on his audience orientation response including absolute separation of pleasurable fear from masochism, nonspecific use of terms such as “audience,” rejection of gorefests as arousing sadistic joys, and inapplicability. While gorefests can provoke masochism and sadism to generate pleasurable fear, this does not make the subgenre or its viewers immoral. An individual can experience sadistic and masochistic pleasures. If the response couples role play and aesthetic distance, it does not harm reactive attitudes. I conclude by demonstrating the applicability of this proposal alongside its place enriching larger discourse on censorship and bias.